Artists Identification Using Convolutional Sparse Autoencoder - Putri, Vinnia Kemala; Indra Kurniadi, Felix (2019 5th International Conference on Computing Engineering and Design (ICCED), 2019)
This paper describes a method to identify artists with a similar painting technique using a semi-unsupervised learning approach. In this paper, we compared Van Gogh and Paul Gauguin since both use impasto painting technique. The contribution of this paper lies in the use of Convolutional Sparse Autoencoder to classify Van Gogh and Paul Gauguin's paintings. The dataset consists of 450 Paul Gauguin's paintings and 716 Van Gogh's paintings. The best result was achieved by using 100 hidden neurons with test accuracy 63.85%, precision 64.12%, and recall 63.85%.